Memorandum on home treatment service
1940-12-17 1940 1940s 4 pages 2. FREE CHOICE OF DOCTOR. Patients like or dislike particular doctors for a great variety of reasons, most of which have very little to do with the skill which the doctor places at their service. Nevertheless, the offer of free service proves quite enough to persuade them to accept with complacency, if not with gratitude, the service of any doctor who chances to turn up at the local clinic. In populous districts it may be possible to allow free choice, so long as this does not mean that one doctor is overworked while another has insufficient occupation. In other districts no choice may be possible. Free choice is almost impossible in many country districts to-day. The Union therefore maintains that free choice of doctor should be provided as far as possible, amongst the doctors in the Service, but will of necessity be limited in sparsely populated areas. 3. RECRUITING OF MEDICAL OFFICERS. When the new system comes into operation all doctors actually in general practice will be given an opportunity to join it. Medical Officers of the Naval and Military Services and of the Air Force who have retired with a pension, but who have no recent experience of general practice, will be able to apply for employment but will have no prescriptive right to it. Newly registered practitioners, who were not qualified at the inception of the Service, will be given opportunities to join as vacancies occur. Although this Memorandum is restricted to the Home Treatment Service it is recognised that Hospital and Specialist services will also have to be incorporated in the State system. At least two years' experience in these hospitals will be regarded as desirable before the newly registered practitioner is accepted for the Home Service. It is quite certain that all such practitioners for several years to come will be absorbed into the Service if they so wish. Both men and women Medical Officers will be required and will be offered the same terms. The single or married status of women Medical Officers will not of itself affect their conditions of service, which will depend entirely upon the efficient performance of the duties which their position in the Service requires of them. The question of special "Motherhood Leave" is one of detail which cannot be settled at this early stage. The position of the doctor who is actually in practice when the Service comes into being, but who is over the retiring age of the Service, has given rise to several questions. It is governed by the statement already made that all doctors actually in practice will then be given an opportunity to join the Service. Such practitioners would no doubt be asked to resign as soon as their compensation and pensions had been settled but it does not appear that any particular hardship would thus be imposed upon them. 4. CHOICE OF DISTRICTS. Those who enter the Service at its inception, and can show that they have already formed substantial professional and social connections in the area in which they are practising, will not be asked to remove to a new area. Those who have not previously been in general practice will have choice of districts according to their qualifications. These qualifications will include academic distinction, knowledge of particular types of practice, or of particular areas and age at entrance. Thus a doctor who has been brought up in the country and has a sympathetic knowledge of rural life will find that his claim to be posted to a rural district and, perhaps, to the area in which his father practised would receive careful consideration. On the other hand, a doctor who had special surgical experience would not be posted to a district where it could be of no value, but would be likely to find himself sent to some area in which a small hospital would give him a chance to combine general practice with responsible surgical work. The particular needs and wishes of more elderly doctors, e.g., new entrants who had retired from the military services, would be met as far as possible by allotting them to posts in which no undue call would be imposed upon their strength. These are only examples of the adjustments which will be required in the broad interests of good service. It will also be necessary to allow transfers from one area to another where a doctor's choice, or the needs of the service, make this desirable. In the early days of the service it will undoubtedly be necessary to increase the medical population of industrial areas, while residents in high class residential areas will find that there are fewer doctors available than hitherto. In epidemic periods temporary transfers will be necessary and it is possible that some doctors may prefer to spend most of their time as locums. Vacancies in the service, in positions calling for some 292/847/1/23